Tradisonalisme sebagai Kritik terhadap Modernisme: Studi Pemikiran Frithjof Schuon - Syamsuri Syamsuri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 1999)
This writing presents one of the prominent figures of Western intellectualism, Frithjof Schuon, who vehemently criticizes Western modernism while advocating traditionalism as a solution. There are several reasons that demonstrate the significance of Schuon's discussion in relation to modernity. Firstly, Schuon is an intellectual who was born, raised, and directly engaged with Western civilization. Therefore, his authority in discussing Western civilization is unquestionable. Secondly, Schuon is a recognized expert in Comparative Religion, known for his proficiency in explaining various religions. This is acknowledged by the adherents of the religions he describes. Due to his expertise, Schuon's thoughts, including traditionalism, are widely listened to and even followed not only by the Islamic community—the religion Schuon eventually chose and adhered to—but also by followers of other religions such as Judaism, Christianity, and others.